Living in Limbo : Conflict-Induced Displacement in Europe and Central Asia - Holtzman, Steven B.; Nezam, Taies (Washington, DC: World Bank, 2013)
The objective of the study is to analyze conflict-induced displacement from the point of view of vulnerability, using a multifaceted definition of vulnerability. As many as 10 million people have been displaced by war in the Europe and Central Asia region since 1990. While many people have been able to return home, approximately half remain displaced, with no available avenues for sustainable reintegration. Currently, in five countries of the region (Armenia, Azerbaijan, Bosnia and Herzegovina, Georgia, and Serbia and Montenegro) displaced persons (DPs) represent more than 5 percent of the total population. In two other countries (Russia and Turkey), they represent high proportions of the population in specific regions (Ingushetia, southeast Turkey). A detailed analysis of the causes and characteristics of displacement-induced vulnerability, Living in Limbo provides pragmatic operational recommendations for policy-makers and practitioners in both development and humanitarian agencies.